EFFICACY OF STREPTOCOCCUS AGALACTIAE WHOLE CELL VACCINE WITH ARTEMIA SP. VECTOR FOR THE PREVENTION OF STREPTOCOCCOSIS IN TILAPIA (OREOCHROMIS NILOTICUS) - Rusli, Rusli; Suryati , Suryati; Mulyati , Mulyati (ITScience (Information Technology and Science), 2022)
This study aims to examine the efficacy of S. agalactiae whole cell vaccine orally with Artemia sp as a vaccine vector for prevention against Streptococcosis in tilapia. Fish fry used in the study were 2-3 cm in size that did not carry S. agalactiae bacteria, kept in 3 l volume jars as many as ten heads / jars. Giving the vaccine to fish orally by first soaking the vaccine into Artemia sp.. The length of soaking time of the vaccine is 15, 30, 60, 90, 120 and 150 minutes. The parameters observed were relative percent survival (RPS), antibody titer value, total leukocytes, pagocytic index, and leukocyte differential. The results of the RPS value study showed that the treatment between vaccines was not significantly different, while the treatment of vaccines with controls was significantly different (P<0.05). The highest RPS value was obtained in vaccine immersion treatment in Artemia sp. for 30 minutes and 120 minutes with a value of 93.33%. Furthermore, RPS is 86.67% at 15 and 150 minutes soaking and RPS is 80% at 30 minutes immersion. This shows that the level of vaccine protection against streptococcosis in tilapia fry is very high